Qualité et sécurité des services de santé offerts en situation linguistique minoritaire en Ontario : investigations des données administratives de santé. - Reaume, Michael; Batista, Ricardo; Prud’homme, Denis; Tanuseputro, Peter (Minorités linguistiques et société, 2024)
Dans cet article, nous présentons une synthèse de plusieurs analyses récentes réalisées par notre groupe de recherche à partir de données administratives de santé pour mesurer la qualité et la sécurité des services de santé offerts aux francophones et allophones en Ontario, Canada. Les résultats de nos analyses démontrent que les Ontariennes et les Ontariens qui reçoivent des soins dans leur principale langue d’usage ont généralement de meilleurs résultats cliniques comparés à ceux qui reçoivent des soins dans une langue autre que leur principale langue d’usage. Ceci suggère que la qualité et la sécurité des soins offerts aux patients et aux patientes en situation de discordance linguistique pourraient être améliorées par le pairage de professionnel-patient parlant la même langue, par exemple, en référant un patient à un médecin qui parle la langue du patient, ou en s’assurant que les francophones ont accès aux services en français en milieux désignés en Ontario en vertu de la Loi sur les services en français et que les allophones puissent bénéficier de davantage de services d’interprétariat. Mots-clés : allophones, données administratives de santé, francophones, minorités de langue officielle, minorités linguistiques, qualité et sécurité des soins de santé

In-hospital patient harm across linguistic groups: A retrospective cohort study of home care recipients - Reaume, Michael; Batista, Ricardo; Talarico, Robert; Guerin, Eva; Rhodes, Emily; Carson, Sarah; Prud'homme, Denis; Tanuseputro, Peter (Journal of patient safety, 2022)
Objective Research examining the impact of language barriers on patient safety is limited. We conducted a population-based study to determine whether patients whose primary language is not English are more likely to experience harm when admitted to hospitals in Ontario, Canada. Methods We used linked administrative health records to establish a retrospective cohort of home care recipients (from 2010 to 2015) who were subsequently admitted to hospital. Patient language (obtained from home care assessments) was coded as English, French, or other. Harmful events were identified using the Hospital Harm Indicator developed by the Canadian Institute for Health Information. Results We included 190,724 patients (156,186 Anglophones, 5,110 Francophones, and 29,428 Allophones). There was no significant difference in the unadjusted risk of harm for Francophones compared with Anglophones (relative risk [RR], 0.94; 95% confidence interval [CI], 0.87–1.02). However, Allophones were more likely to experience harm when compared with Anglophones (RR, 1.14; 95% CI, 1.10–1.18). The risk of harm was even greater for Allophones with low English proficiency (RR, 1.18; 95% CI, 1.13–1.24). After adjusting for potential confounders, Anglophones and Allophones were equally likely to experience harm of any type, but Allophones more likely to experience harm from infections and procedures. Conclusions Patients whose primary language was not English or French were more likely to experience harm after admission to hospital, especially if they had low English proficiency. For these patients, the risk of harm from infections and procedures persisted in the adjusted analysis, but the overall risk of harm did not.

The impact of language on emergency department visits, hospitalizations, and lenght of stay among home care recipients - Reaume, M.; Batista, Ricardo; Rhodes, Emily; Knight, Braden; Imsirovic, Haris; Seale, Emily; Riad, Karine; Prud'homme, Denis; Tanuseputro, Peter (Medical care, 2021)
Background: Research considering the impact of language on health care utilization is limited. We conducted a population-based study to: (1) investigate the association between residents’ preferred language and hospital-based health care utilization; and (2) determine whether this association is modified by dementia, a condition which can exacerbate communication barriers. Methods: We used administrative databases to establish a retrospective cohort study of home care recipients (2015–2017) in Ontario, Canada, where the predominant language is English. Residents’ preferred language (obtained from in-person home care assessments) was coded as English (Anglophones), French (Francophones), or other (Allophones). Diagnoses of dementia were ascertained with a previously validated algorithm. We identified all emergency department (ED) visits and hospitalizations within 1 year. Results: Compared with Anglophones, Allophones had lower annual rates of ED visits (1.3 vs. 1.8; P<0.01) and hospitalizations (0.6 vs. 0.7; P<0.01), while Francophones had longer hospital stays (9.1 vs. 7.6 d per admission; P<0.01). After adjusting for potential confounders, Francophones and Allophones were less likely to visit the ED or be hospitalized than Anglophones. We found evidence of synergism between language and dementia; the average length of stay for Francophones with dementia was 25% (95% confidence interval: 1.10–1.39) longer when compared with Anglophones without dementia. Conclusions: Residents whose preferred language was not English were less frequent users of hospital-based health care services, a finding that is likely attributable to cultural factors. Francophones with dementia experienced the longest stays in hospital. This may be related to the geographic distribution of Francophones (predominantly in rural areas) or to suboptimal patient-provider communication.

Ascertaining the Francophone population in Ontario: validating the language variable in health data - Batista, Ricardo; Hsu, Amy T.; Bouchard, Louise; Reaume, Michael; Rhodes, Emily; Sucha, Ewa; Guerin, Eva; Prud'homme, Denis; Manuel, Douglas G.; Tanuseputro, Peter (BMC Medical Research Methodology, 2024)
Abstract Background Language barriers can impact health care and outcomes. Valid and reliable language data is central to studying health inequalities in linguistic minorities. In Canada, language variables are available in administrative health databases; however, the validity of these variables has not been studied. This study assessed concordance between language variables from administrative health databases and language variables from the Canadian Community Health Survey (CCHS) to identify Francophones in Ontario.

Patient-Physician Language Concordance and Cardiovascular Outcomes Among Patients With Hypertension. - Reaume, Michael; Labossière, Mathieu N.; Batista, Ricardo; Van Haute, Stephanie; Tangri, Navdeep; Rigatto, Claudio; Bohm, Clara; Prud’homme, Denis; Tanuseputro, Peter; Lix, L. M. (JAMA Network Open, 2025)
Importance Patients who live in minority language communities often receive health care services of lower quality and safety compared with patients who speak the majority language. Yet the outcomes associated with care provided by physicians who speak a patient’s primary language remain unknown. Objective To examine patient-physician language concordance and the risk of major adverse cardiovascular events (MACEs) among patients with hypertension. Design, Setting, and Participants This retrospective cohort study identified adults with self-reported hypertension in the Canadian Community Health Survey, a national survey that collects data from a representative sample of Canadians, from January 1, 2003, to December 31, 2014. Respondents (excluding those living in Quebec) had their hospitalization and mortality records linked to their survey responses. Data were analyzed from October 2023 to May 2024. Exposures Respondents’ primary home language was defined using language spoken most often at home. Language spoken with a regular physician was used to measure patient-physician language concordance. Respondents who spoke to their regular physician in their primary home language were classified as having received language-concordant care, while all other respondents were classified as having received language-discordant care.

Patient-physician language concordance and quality and safety outcomes among frail home care recipients admitted to hospital in Ontario, Canada - Seale, Emily; Reaume, Michael; Batista, Ricardo; Eddeen, Anan. Bader; Roberts, Rihannon; Rhodes, Emily; McIsaac, Daniel. I.; Kendall, Claire. E.; Sood, Manish. M.; Prud'homme, Denis; Tanuseputro, Peter (Canadian Medical Association Journal, 2022)
Background: When patients and physicians speak the same language, it may improve the quality and safety of care delivered. We sought to determine whether patient–physician language concordance is associated with in-hospital and postdischarge outcomes among home care recipients who were admitted to hospital. Methods: We conducted a population-based study of a retrospective cohort of 189 690 home care recipients who were admitted to hospital in Ontario, Canada, between 2010 and 2018. We defined patient language (obtained from home care assessments) as English (Anglophone), French (Francophone) or other (allophone). We obtained physician language from the College of Physicians and Surgeons of Ontario. We defined hospital admissions as language concordant when patients received more than 50% of their care from physicians who spoke the patients’ primary language. We identified in-hospital (adverse events, length of stay, death) and post-discharge outcomes (emergency department visits, readmissions, death within 30 days of discharge). We used regression analyses to estimate the adjusted rate of mean and the adjusted odds ratio (OR) of each outcome, stratified by patient language, to assess the impact of language-concordant care within each linguistic group. Results: Allophone patients who received language-concordant care had lower risk of adverse events (adjusted OR 0.25, 95% confidence interval [CI] 0.15–0.43) and in-hospital death (adjusted OR 0.44, 95% CI 0.29–0.66), as well as shorter stays in hospital (adjusted rate of mean 0.74, 95% CI 0.66–0.83) than allophone patients who received language-discordant care. Results were similar for Francophone patients, although the magnitude of the effect was smaller than for allophone patients. Language concordance or discordance of the hospital admission was not associated with significant differences in postdischarge outcomes.

Évaluer le potentiel de soins linguistiquement concordants pour les francophones de l’Ontario : une étude populationnelle transversale. - Carr, Kady; Batista Moliner, Ricardo; Fitzgerald, Michael; Lamontagne, Sophie; Bader Eddeen, Anan; Timony, Patrick E.; Bédard, Daniel; Gauthier, Alain; Prud’homme, Denis; Landry, Josette-Renée; Chomienne, Marie-Hélène; Denis-Leblanc, Manon; et al. (Minorités linguistiques et société, 2024)
Cette étude a utilisé les données sur les médecins, la facturation et le recensement de 2016 dont dispose l’ICES pour examiner l’accès potentiel à des médecins de famille francophones pour les francophones résidant dans 1 643 aires de diffusion agrégées (ADA) de l’Ontario. L’Ontario compte 550 280 francophones, soit 4,1 % de sa population. Nous avons identifié 8 199 médecins de famille, parmi lesquels 1 169 se sont autodéclarés francophones. Le ratio provincial global pour les francophones était de 2,12 médecins par 1 000 résidentes et résidents, comparativement à un ratio de 0,66 pour les anglophones. Dans les ADA où les francophones étaient majoritaires, le ratio pour les francophones était inférieur au ratio pour les anglophones (0,63 vs 2,02), alors que dans toutes les autres ADA, le ratio francophone était plus élevé (3,46 vs 0,62 dans les 83,4 % des ADA où les francophones représentaient >0 % à <5 % de la population). Huit ADA du Nord-Est et de l’Est de l’Ontario présentaient un déficit relatif important de médecins de famille francophones par rapport au ratio provincial. Ces résultats donnent un aperçu des régions qui pourraient bénéficier de programmes visant à éliminer les barrières linguistiques. Mots-clés : Concordance linguistique, médecins de famille, accès aux soins primaires, francophones, Ontario